Development of Mathematics Song Lyrics on Whole Numbers for Students With Special Needs - Nia Wahyu Damayanti; Eko Yuniarto; Elisabeth Rambu Mura; Abdul Hamid Bachtiar (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the development and effectiveness of math song lyrics as a pedagogical tool to enhance the learning experiences of students with special needs in Class XC Tunagrahita. The research follows the Plomp development model, comprising three stages: preliminary research, prototyping, and assessment. During the preliminary research phase, observations and interviews were conducted to gather information on classroom learning processes. The prototyping phase involved creating song titles, intros, and verses tailored to the students' needs. In the assessment phase, the product was evaluated using expert validation sheets. Data collection methods included observation, interviews, and documentation. Findings indicate that the developed math song lyrics, focused on numerical material, are suitable for use in the classroom. The validation process confirmed the lyrics' appropriateness and potential to support the learning needs of students with intellectual disabilities. The study underscores the utility of integrating music into mathematics education for special needs students, providing an engaging and accessible learning medium. Math song lyrics designed through a structured development model can serve as an effective educational resource for enhancing learning outcomes among students with special needs. Further research could explore the long-term impacts of this approach and its application across different subjects and student populations.